2002
DOI: 10.1002/polb.10106
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics and moisture sorption behavior of nylon‐6/clay hybrid films

Abstract: The structure of nylon‐6 hybrids with synthetic or natural clays was investigated for melt‐pressed films with Fourier transform infrared spectroscopy, wide‐angle X‐ray diffraction, and differential scanning calorimetry in comparison with the nylon‐6 homopolymer. In contrast to the development of familiar α‐form crystals in plain nylon‐6 film, the hybrid films produced γ‐form crystals when nylon‐6 was conjugated with synthetic mica, whereas the hybridization with natural montmorillonite gave rise to both α‐ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 25 publications
3
30
0
Order By: Relevance
“…The results reported in Table 2 show at first that the crystallinity degree values and the gas permeability coefficients determined on the neat matrices are in good agreement with those commonly reported in the literature [17,21,33]. PA matrix is characterized by enhanced gas barrier properties despite its lower crystallinity rate.…”
Section: Binary Systems: Pa/mmt-oh and Pe/mmt-tallowsupporting
confidence: 87%
See 1 more Smart Citation
“…The results reported in Table 2 show at first that the crystallinity degree values and the gas permeability coefficients determined on the neat matrices are in good agreement with those commonly reported in the literature [17,21,33]. PA matrix is characterized by enhanced gas barrier properties despite its lower crystallinity rate.…”
Section: Binary Systems: Pa/mmt-oh and Pe/mmt-tallowsupporting
confidence: 87%
“…A lot of attention has been particularly paid these last years on nanofillers such as clays to reinforce PA or PE properties [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Indeed due to their high aspect ratio and their impermeable character, the clay platelets are expected to induce significant tortuosity effects when they are dispersed within a polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…A larger endothermic peak could be observed at around T = 226°C which is associated with the melting of both α and γ form crystals of PA6 as compared to the neat PA6 which shows a single sharp peak. The broadness of the peak is due to the effect of the organoclay on the crystallinity of PA6 similar effect was reported by Picard et al [20] where they found that the percent crystallinity was not affected by the addition of the organoclay however, Murase et al [21] find that It can be concluded form both DSC and XRD measurement that no major modification of the PA6 crystallinity did occur by the introduction of the organoclay even if an alteration of the peak was observed which may be due to the increase of the γ phase. It is believed that the organoclay did not affect the crystallinity of the PA6 which may not alter the moisture absorption as the diffusion may just occur in the amorphous region of PA6 and not within the crystalline ones and the only effect will be the one of the organoclay and the way to prevent the diffusion of water within the matrix.…”
Section: Effects Of Clay On Polyamide 6 Crystallizationmentioning
confidence: 52%
“…Confinement effects are well known and have been described elsewhere. [14][15][16] Significant alterations in crystallite morphology [11,13,[17][18][19][20][21][22][23][24][25][26] and orientation, [11,13,17,18,21,24,[26][27][28] as well as the crystalline phase(s) present, [11,13,21,[26][27][28][29][30][31][32][33][34][35][36] will also affect the materials properties. Finally, the flexible nature of these layers [37] and their propensity to align at high strains [11,13,[26][27][28][38][39][40][41] and to induce void formation at high stresses [17,…”
Section: Introductionmentioning
confidence: 99%